Volume 2D: Turbomachinery 2014
DOI: 10.1115/gt2014-26921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endwall Boundary Layer Thickness on Losses in a LPT Cascade With Unsteady Wakes

Abstract: The effects of inlet endwall boundary layer thickness and up-stream unsteady wakes are investigated experimentally in a low-speed linear cascade. The examined airfoil is the front-loaded L2F, a high-lift low-pressure turbine profile with high resistance to separation even in the low Reynolds number regime. Cases are documented with and without incoming wakes for two inlet endwall boundary layers of different thickness at a Reynolds number of Re = 30,000. Periodic incoming wakes are simulated with moving bars u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Figure 15(a) shows the loss variation along the spanwise direction at the exit (x/C x = 1.3). Three loss cores are identified in all of the 6 In other words, larger velocity gradient. cases.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 15(a) shows the loss variation along the spanwise direction at the exit (x/C x = 1.3). Three loss cores are identified in all of the 6 In other words, larger velocity gradient. cases.…”
Section: Resultsmentioning
confidence: 97%
“…Effect of inflow conditions : de la Blanco et al (2003) reported that the state of the incoming endwall boundary layer plays an important role in endwall loss generation. By simulating the wakes using upstream moving bars, Steurer et al (2014) studied the effects of incoming wakes on the secondary flow. The effect of secondary flow from the upstream blade row was not considered in this study.…”
Section: Othersmentioning
confidence: 99%
“…The objectives of these studies can be broadly classified into understanding the: a) endwall flow features, b) loss generation mechanisms and c) effect of inflow conditions. A brief 15 review of the relevant literature is given below:…”
Section: Introductionmentioning
confidence: 99%
“…Effect of inflow conditions: Blanco et al [14] reported that the state of the in-40 coming endwall boundary layer plays an important role in endwall loss generation. By simulating the wakes using upstream moving bars, Steurer [15] studied the effects of incoming wakes on the secondary flow. The effect of secondary flow from the upstream blade row was not considered in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation